Alleviating psychological distress via social media: the voices from working-from-home Malaysian women - Ariffin, Adlina; Abdul Khaiyom, Jamilah Hanum; Kartiwi, Mira; Azizan, Awis Rumaisya (Institut Penyiaran dan Penerangan Tun Abdul Razak(IPPTAR), 2022)
When Covid-19 outbreak hit the world, all countries were forced to be in strict quarantine for a period of time. This unforeseen event greatly impacted working women who made up 38.9% or 5.83 million of the total workforce in Malaysia as they were forced to work from home (WFH) on top of performing other different roles; a wife, mother, daughter as well as caretaker. There were no explicit guidelines in terms of time, space and roles in fulfilling the household and professional duties. This led them to experience psychological distress. Using a mixed- method approach via the use of open-ended questionnaires and online semi-structured interviews, this study investigated the challenges faced by these women, specifically those who live in urban and rural areas and how they used social networks to alleviate their distress. The findings indicate that women from both areas faced similar challenges and used the social networks correspondingly to overcome those challenges. Being informed of this situation will help our working women to be more prepared and resilient should a similar global pandemic emerge in the future.